Implementasi Pelayanan Hak Tanggungan Terintegrasi Secara Elektronik di Kantor Pertanahan Kota Batam - Exaudia, Sara; Wahyuni, Wahyuni; Nurasa, Akur (Marcapada: Jurnal Kebijakan Pertanahan, 2021)
Economic growth in line with service modernization requires the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) complete assigned efficiently, accurately, and effectively. To improve service quality, digital and integrated transformation are required. This has been accomplished by using electronically integrated Mortgage Rights (HT-el) services. Batam City Land Office has been operating HT-el services as one of the pilot projects since September 2019. Therefore, this study discusses how HT-el was implemented at Batam City Land Office. This study aimed to determine the suitability of Batam City Land Office's implementation of HT-el services with ATR/BPN Ministry Regulation Number 5 of 2020, the implementation’s obstacles, and the solutions. This study used qualitative method with descriptive approach. The findings indicated that the implementation of HT-el in Batam City Land Office has been completed in accordance with the HT-el service stages of preparation, implementation, and evaluation, such that the implementation of HT-el in Batam City Land Office complies with ATR/BPN Ministry Regulation Number 5 of 2020. Constraints encountered and resolve efforts are: (1) disruption of the HT-el system; (2) omission of debtors with different guarantors; (3) errors in HT ranking data; and (4) the file was canceled due to non-compliance.